A VERSATILE MULTIMEDIA SOFTWARE FOR WIND ENERGY EDUCATION - Samarakou, Maria; Fylladitakis, Emmanouil D.; Karolidis, Dimitrios (European Scientific Journal, ESJ, 2013)
With the advancement of technology and the spreading access to the internet, computer-assisted education is taking leaps forward. Multimedia has been known for years to be a powerful technological tool to enhance human learning and technological advancement today allows the quick adaptation of educational material into multimedia systems, as well as the streaming of such material through internet connections. This paper is aiming to present a versatile, yet simple to use and lightweight on computer resources multimedia educational application on wind energy resources and technologies, which can be easily adopted for a multitude of educational scenarios.